Comparison of three and four point bending evaluation of two adhesive bonding systems for glass-ceramic zirconia bi-layered ceramics. Issue 9 (September 2017) - Gee, C.; Weddell, J.N.; Swain, M.V.
Abstract: Objectives: To quantify the adhesion of two bonding approaches of zirconia to more aesthetic glass-ceramic materials using the Schwickerath (ISO 9693-2:2016) three point bend (3PB) [1] test to determine the fracture initiation strength and strain energy release rate associated with stable crack extension with this test and the Charalamabides et al. (1989) [2] four point bend (4PB) test. Methods: Two glass-ceramic materials (VITABLOCS Triluxe forte, Vita Zahnfabrik, Germany and IPS.emax CAD, Ivoclar Vivadent, Liechtenstein) were bonded to sintered zirconia (VITA InCeram YZ). The former was resin bonded using a dual-cure composite resin (Panavia F 2.0, Kuraray Medical Inc., Osaka, Japan) following etching and silane conditioning, while the IPS.emax CAD was glass bonded (IPS e.max CAD Crystall/Connect) during crystallization of the IPS.emax CAD. Specimens (30) of the appropriate dimensions were fabricated for the Schwickerath 3PB and 4PB tests. Strength values were determined from crack initiation while strain energy release rate values were determined from the minima in the force-displacement curves with the 3PB test (Schneider and Swain, 2015) [3] and for 4PB test from the plateau region of stable crack extension. Results: Strength values for the resin and glass bonded glass ceramics to zirconia were 22.20 ± 6.72 MPa and 27.02 ± 3.49 MPa respectively. The strain energy release rates for the two methods used were very similar and for the glass bonding, (4PB) 15.14 ± 5.06 N/m (or J/m 2 ) and (3PB) 16.83 ± 3.91 N/m and resin bonding (4PB) 8.34 ± 1.93 N/m and (3PB) 8.44 ± 2.81 N/m respectively. The differences in strength and strain energy release rate for the two bonding approaches were statistically significant (p < 0.05). SEM observations showed fracture occurred adhesively for the resin bonding and cohesively for the glass bonding. Significance: The present results indicate 3PB and 4PB tests have very similar values for the strain energy release rate determination. However while strength tests reveal minimal differences between resin and glass bonding, strain energy release rates for the latter are superior for bonding CAD/CAM milled glass-ceramics to zirconia.